Public Participation, Teacher Accountability, And School Outcomes : Findings From Baseline Surveys In Three Indian States - Pandey, Priyanka, 1986- 1986- (The World Bank, 2008)
This paper presents findings from baseline surveys on student learning achievement, teacher effort and community participation in three Indian states, Karnataka, Madhya Pradesh and Uttar Pradesh. Results indicate low teacher attendance and poor student learning. Parents and school committees are neither aware of their oversight roles nor participating in school management. However, there is substantial heterogeneity in outcomes across states. Karnataka has better student and teacher outcomes as well as higher levels of community awareness and participation than the other two states. The authors find substantial variation in teacher effort within schools, but most observable teacher characteristics are not associated with teacher effort. One reason for low teacher effort may be lack of accountability. Regression analysis suggests low rates of teacher attendance are only part of the problem of low student achievement. The gains in test scores associated with higher rates of attendance and engagement in teaching are small in the states of Madhya Pradesh and Uttar Pradesh, suggesting teachers themselves may not be effective. Ineffective teaching may result from lack of accountability as well as poor professional development of teachers. Further research is needed to examine not only issues of accountability but also professional development of teachers